Profil Peternak Rakyat Sapi Perah Peranakan Friesien Holstein Laktasi Pada Kelompok Ternak Desa Pesanggrahan, Kota Batu - Ariani Trisna Murti; Rosyida Fajri Rinanti; Hidayati Karamina (Jurnal Ilmiah Fillia Cendekia, 2022)
This research was conducted on February 1, 2022 to March 1, 2022 in the PFH Lactation cattle group in Pesanggrahan Village, Batu City. Pesanggrahan Village Community. The research objectives of the formulation of the problem are 1) to analyze and find out how the profile of smallholder dairy farmers of Friesien Holstein lactation in the lactating PFH cattle group in Pesanggrahan Village, Batu City. 2) to analyze and determine the milk production of lactating Friesien Holstein Crossbreeds in the Lactation PFH Cattle group in Pesanggrahan Village, Batu City. This type of descriptive research is research conducted by searching/exploring (exploration) and an action that aims to obtain explanations and clarification of certain problems (clarification) regarding a phenomenon or social reality. The dairy farmer profile includes: 1) Respondent's identity, namely education level, age, sex, and length of breeding, 2) Ownership scale of Friesien Holstein Lactation cattle, 3) Type of feeding, and 4) Frequency of feeding. The conclusions that can be drawn during the implementation of the study are 1) The profile of smallholder dairy farmers of PFH Lactation are of productive age, with the most recent education level being elementary school. Most breeders have more than 10 years of experience and are dominated by small-scale small-scale farmers, 2) Dairy cow milk production in Pesanggrahan Village is on a medium – low scale, with the highest number in Toyomerto Hamlet. The density of milk in Pesanggrahan Village is still relatively low. Keywords: profile of smallholder farmers, PFH dairy cows, lactation, milk production